2012
DOI: 10.1093/aobpla/pls011
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor OsHsfC1b regulates salt tolerance and development in Oryza sativa ssp. japonica

Abstract: The paper describes the functional analysis of a class C heat shock transcription factor from rice (Oryza sativa). OsHsfC1b is shown to play a role in ABA-mediated salt stress tolerance and is required for plant growth under non-stress conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 69 publications
(92 reference statements)
0
54
0
Order By: Relevance
“…Subsequently, multistep PCR was performed as described previously (Warthmann et al, 2008). The artificial microRNA construct was cloned into pC5300 OE vector according to Schmidt et al (2012). For construction of SERF1 overexpression lines, the full-length CDS of SERF1 was synthesized and sequence verified by GeneArt.…”
Section: Constructs and Rice Transformationmentioning
confidence: 99%
“…Subsequently, multistep PCR was performed as described previously (Warthmann et al, 2008). The artificial microRNA construct was cloned into pC5300 OE vector according to Schmidt et al (2012). For construction of SERF1 overexpression lines, the full-length CDS of SERF1 was synthesized and sequence verified by GeneArt.…”
Section: Constructs and Rice Transformationmentioning
confidence: 99%
“…The functional characterization of a class C Hsf has been reported recently in Oryza sativa (Os). OsHsfC1b serves as a regulator of salt stress response and affects plant growth under non-stress conditions [31]. Moreover, previous studies have indicated that HsfA4 has a negative correlation with the levels of ascorbate peroxidase 1 (APX1) and may function as an anti-apoptotic factor in plants [32], [33], [34].…”
Section: Introductionmentioning
confidence: 99%
“…WMD computationally generates hundreds of amiRNAs for each target that are ranked based on the complementarity and hybridization energy without knowing the in vivo effi ciency. The effi cacy of amiRNAs has been tested in Arabidopsis (Schwab et al 2006 ), rice (Warthmann et al 2008 ;Schmidt et al 2012 ), Physcomitrella patens (Khraiwesh et al 2008 ), Chlamydomonas reinhardtii (Molnar et al 2009 ), and other species. The advantages of amiRNA compared to other RNA silencing approaches such as RNA interference (RNAi) and virusinduced gene silencing (VIGS) are that it has minimal off-target effects and a unique capacity for multigene silencing (Alvarez et al 2006 ;Niu et al 2006 ;Schwab et al 2006 ;Ossowski et al 2008 ).…”
Section: Artifi Cial Micrornas (Amirnas)mentioning
confidence: 99%